2018
DOI: 10.1159/000488821
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-381 Favors Repair of Nerve Injury Through Regulation of the SDF-1/CXCR4 Signaling Pathway via LRRC4 in Acute Cerebral Ischemia after Cerebral Lymphatic Blockage

Abstract: Background/Aims: Acute cerebral ischemia is a manifestation of cerebral vascular insufficiency and has a high mortality. However, the therapy for acute cerebral ischemia is still limited. This study aimed to investigate the effect of microRNA-381 (miR-381) on the repair of nerve injury in rats with acute cerebral ischemia after cerebral lymphatic blockage (CLB) by targeting leucine-rich repeat C4 protein (LRRC4) through the Stromal cell-derived factor-1/CXC chemokine receptor-4 signaling pathway. Methods: Rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Rats were allocated into 6 groups (n = 6) and injected with plasmid or miR into lateral cerebroventricular before the establishment of MCAO models, including the sham group, the MCAO group (modeled rats), the NC group (modeled rats with lateral cerebroventricular injection of 5 μL scrambled oligonucleotides [100 μM]), the miR-326-5p agomir group (modeled rats with lateral cerebroventricular injection of 5 μL miR-326-5p agomir [100 μM]), the sh-STAT3 group (modeled rats with lateral cerebroventricular injection of 5 μL STAT3 interference vector [100 μM]) and the miR-326-5p agomir + oe-STAT3 group (modeled rats with lateral cerebroventricular injection of 5 μL miR-326-5p agomir [100 μM] and 5 μL STAT3 overexpression vector [100 μM]) [20,21].…”
Section: Rat Model Establishmentmentioning
confidence: 99%
“…Rats were allocated into 6 groups (n = 6) and injected with plasmid or miR into lateral cerebroventricular before the establishment of MCAO models, including the sham group, the MCAO group (modeled rats), the NC group (modeled rats with lateral cerebroventricular injection of 5 μL scrambled oligonucleotides [100 μM]), the miR-326-5p agomir group (modeled rats with lateral cerebroventricular injection of 5 μL miR-326-5p agomir [100 μM]), the sh-STAT3 group (modeled rats with lateral cerebroventricular injection of 5 μL STAT3 interference vector [100 μM]) and the miR-326-5p agomir + oe-STAT3 group (modeled rats with lateral cerebroventricular injection of 5 μL miR-326-5p agomir [100 μM] and 5 μL STAT3 overexpression vector [100 μM]) [20,21].…”
Section: Rat Model Establishmentmentioning
confidence: 99%
“…SDF-1 is a chemokine that has a strong chemotactic effect on EPCs. After vascular injury, SDF-1 induces migration of EPCs to the injured area and promotes endothelialization [20,21]. Under hyperglycemic conditions miR-133a was found to be up-regulated and induced endothelial dysfunction through inhibition of eNOS [22].…”
Section: Discussionmentioning
confidence: 95%
“…SDF-1 is a chemokine that has a strong chemotactic effect on hematopoietic stem/endothelial cells. After vascular injury, a high SDF-1 concentration gradient can form locally, thereby inducing endothelial progenitor cells to mobilize from the bone marrow along the concentration gradient to the periphery, further homing to the vascular injury area, and promoting endothelialization repair through adhesion, angiogenesis, and paracrine signals (22,23). Our study showed that sitagliptin promoted not only the migration and angiogenesis of endothelial progenitor cells but also the expression of the provascular cytokines SDF-1 and VEGF by endothelial progenitor cells at the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%